Adaptive Hypermedia and Adaptive Web-Based Systems - Nejdl, Wolfgang (Springer, 2017)
This book constitutes the refereed proceedings of the 5th International Conference on Adaptive Hypermedia and Adaptive Web-Based Systems, AH 2008, held in Hannover, Germany in July 2008.